The Relationship Between Age and Subjective Well-Being: Evidence from Five Capital Cities in Mainland China - Xing, Zhanjun; Huang, Liqing (Social indicators research, 2014)
Since the mid-60s of the twentieth-century, the researchers have made lots of studies on the relationship between age and subjective well-being (SWB), and yielded some contradictory conclusions. By using an urban sample (N = 3,099) from five capital cities in Mainland China, this paper presents some new evidence on this issue in the Chinese context. The paper reconfirms a significant relationship between age and subjective well-being, and argues that different measure instruments of subjective well-being lead to different types of relationship. It is partly testified that subjective well-being follows approximate U-shape across age groups, and the minimum point lies in the age band 45–49. It is also found that age is not always a strong significant predictor of subjective well-being when a different dependent variable was adopted to multiple regression analysis. It is suggested that the researchers should pay more attention to the specific content of subjective well-being while examining the relationship between age and subjective well-being.